STUDYING THE HISTORY OF THE STATE OF AMIR TEMUR AND TEMURID AT THE LATE XIX - BEGINNING XX CENTURIES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
After the conquest of the territory of Central Asia by the Russian Empire, the interest of orientalist researchers, historians, as well as military historians and simply collectors in the search and collection of oriental manuscripts reflecting the history of Central Asia, including the period of the reign of Amir Temur and the Temurids, revived.